THE INFLUENCE OF PREMIUM INCOME, UNDERWRITING AND INVESTMENT RESULTS ON PROFITS TOWARDS JOINT VENTURE GENERAL INSURANCE COMPANIES IN INDONESIA - Amani, Zati; Markonah Markonah (Dinasti Publisher, 2020)
The purpose of this research was to analyzed the influence of premium income, underwriting and investment returns on profits towards joint venture general insurance companies in Indonesia. The samples that were used was 8 joint venture general insurance companies with a purposive sampling technique, including: PT ACE Jaya Proteksi, PT Allianz Utama Indonesia's Insurance, PT AIG Insurance Indonesia, PT Mandiri Insurance AXA General Insurance, PT Asuransi MSIG Indonesia, PT Asuransi Sompo Japan Nipponkoa Indonesia, PT Asuransi Tokio Marine Indonesia and PT Asuransi QBE Pool Indonesia. The data used in this research were obtained from the 2011-2016 Indonesian insurance report. And The analysis technique which used in this research is panel data regression. The results of the research were using the fixed effect model found that premium income and underwriting results had a significant positive influences towards the profits of joint venture general insurance companies in Indonesia, while investment results showed no any effection towards its.